Diffusion behavior of Sn atoms in Sn58Bi solder joints under the coupling effect of thermomigration and electromigration. Issue 12 (15th April 2016) - Guo, Fu; Liu, Qian; Ma, Limin; Zuo, Yong
Abstract: Abstract : Thermomigration (TM) and electromigration (EM) are two persistent reliability issues and they generally appear concurrently in solder joints. Many previous studies have attempted to understand the fundamental principles behind these phenomena with the majority of which focusing their interest into the faster migration elements in solders like Bi, Ni, or Cu. However, Sn as the slower migration element has not received that much attention. In the present study, a special linearly symmetrical structure was used. An unusual TM phenomenon of Sn atoms in the Sn58Bi solder joint was observed. The unusual TM of Sn atoms along the vertical edges was attributed to the coupled effect of the EM in the horizontal direction and the TM in vertical direction. The relationships between the microstructural characteristics and the temperature distribution were established. The results also indicated that elevated temperature and sufficient thermal gradient were the two major factors that caused TM.